How do 3-year-olds use relevance inferencing to interpret indirect speech?. Issue 1 (February 2022) - Abbot-Smith, Kirsten; Schulze, Cornelia; Anagnostopoulou, Nefeli; Zajączkowska, Maria; Matthews, Danielle
If a child asks a friend to play football and the friend replies, 'I have a cough', the requesting child must make a 'relevance inference' to determine the communicative intent. Relevance inferencing is a key component of pragmatics, that is, the ability to integrate social context into language interpretation and use. We tested which cognitive skills relate to relevance inferencing. In addition, we asked whether children's lab-based pragmatic performance relates to children's parent-assessed pragmatic language skills. We tested 3.5- to 4-year-old speakers of British English (Study 1: N = 40, Study 2: N = 32). Children were presented with video-recorded vignettes ending with an utterance requiring a relevance inference, for which children made a forced choice. Study 1 measured children's Theory of Mind, their sentence comprehension and their real-world knowledge and found that only real-world knowledge retained significance in a regression analysis with children's relevance inferencing as the outcome variable. Study 2 then manipulated children's world-knowledge through priming but found this did not improve children's performance on the relevance inferencing task. Study 2 did, however, reveal a significant correlation between children's relevance inferencing and a measure of morpho-syntactic production. In both studies parents rated their children's pragmatic language usage in daily life, which was found to relate to performance in our lab-based relevance inferencing task. This set of studies is the first to empirically demonstrate that lab-based measures of relevance inferencing are reflective of children's pragmatic abilities 'in the wild'. There was no clear association between relevance inferencing and Theory of Mind. There was mixed evidence for the role of formal language, which should be further investigated. Finally, real-world knowledge was indeed associated with relevance inferencing but future experimental work is required to test causal relations.